2012
DOI: 10.1017/s1751731111002618
|View full text |Cite
|
Sign up to set email alerts
|

How do sheep affect plant communities and arthropod populations in temperate grasslands?

Abstract: Grasslands being used in sheep farming systems are managed under a variety of agricultural production, recreational and conservational objectives. Although sheep grazing is rarely considered the best method for delivering conservation objectives in seminatural temperate grasslands, the literature does not provide unequivocal evidence on the impact of sheep grazing on pasture biodiversity. Our aim was therefore to review evidence of the impacts of stocking rate, grazing period and soil fertility on plant commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 74 publications
5
19
1
Order By: Relevance
“…Auchenorrhyncha abundance markedly increased in relation to lower stocking densities during the experimental period, with the highest counts observed in the ''Mixed low'' treatment and ''Ungrazed'' control, consistent with the general relationship recorded for this Sub-Order in the literature up until 2010 (Scohier and Dumont, 2012). Taller average swards provide favourable microhabitats for Auchenorrhyncha, especially increased humidity, leaf surface area of host plants and microhabitats (Eyre, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Auchenorrhyncha abundance markedly increased in relation to lower stocking densities during the experimental period, with the highest counts observed in the ''Mixed low'' treatment and ''Ungrazed'' control, consistent with the general relationship recorded for this Sub-Order in the literature up until 2010 (Scohier and Dumont, 2012). Taller average swards provide favourable microhabitats for Auchenorrhyncha, especially increased humidity, leaf surface area of host plants and microhabitats (Eyre, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…For instance, moderate grazing was found to have a positive effect on arthropod diversity in several studies [33] but we found only weak total effects of grazing intensity on arthropod diversity (<0.2). A wider range of grazing intensities in our study system compared to other studies might explain the absence of a positive effect in our case; e.g.…”
Section: Discussioncontrasting
confidence: 69%
“…These results are in line with previous studies that suggested that management effects on plant communities cascade up to reduce the dominance of herbivores in arthropod communities (Scherber et al . ; Scohier & Dumont ). Several traits, however, were not affected by land‐use intensity in our study, as for example the mobility trait in Carabidae and Oribatida, the feeding trait in Carabidae or the stratum trait in all taxa.…”
Section: Discussionmentioning
confidence: 99%